The Effect Of Qardhul Hasan Capital On Micro Business Development Of Islamic Micro Waqf Bank Customers (Research on BWM Syariah Lan Taburo La Tansa Lebak Banten Customers) - Budiman, Budiman; Widasari, Ela (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2023)
Micro and small enterprises are very important in supporting national economic stability. With micro businesses, people can run their economy without having to use regulations made for larger-scale businesses. The role of micro businesses is to reduce poverty and encourage the rate of economic growth. This study aims to determine the effect of capital on the development of micro businesses in customers assisted by the Lan Taburo Lebak Islamic Micro Waqf Bank. The results showed that the micro business of sharia micro waqf bank customers after getting capital from megalami profit development below Rp. 500,000 decreased by 63%, while for micro businesses that received profits of Rp. 500,000 - Rp. 1,000,000 increased by 33%, as well as businesses that received profits of Rp. 1,000,000 - Rp. 1,500,000 increased by 41%, then those that received profits above Rp. 1,500,000 increased by 79%. The average business profit after receiving financing from the Islamic Micro Waqf Bank is 54%. Based on the results of the analysis, it shows that there is a positive and significant effect of capital loans on customer micro business development. While the coefficient of determination test results state that the capital variable can only explain 65.4% of micro business growth while the remaining 34.6% is influenced by other factors.